Energy Audit: A Case Study of an Academic Building - Chakraborty, Mouli; Dolui, Uttam Kr; Ghosh, Debojyoti; Mishra, Subhankar; Jana, Sougata (International Journal of Computer Sciences and Engineering, 2025)
The rapid diminution of fossil fuel resources on a worldwide basis now a days has necessitated an urgent search for alternative energy sources to cater to the present day energy demands. This paper analyzes the proper methodology to calculate the cumulative consumption of energy utilization in an academic building. The opportunities lie in the use of existing renewable energy technologies, greater efforts at energy efficiency and the distribution of these technologies and options. Energy Saving can be done by improved techniques and better instrumentation. It provides a comprehensive eco design of a smooth lighting & electrical system comprising appropriate electrical components which structurally improves the entire energy distribution system towards the destination of achieving energy efficiency